2021
DOI: 10.2147/dddt.s321879
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Alleviates UUO-Induced Inflammation and Fibrosis by Regulating the NF-κB P65/STAT3 and TGFβ1/Smads Signaling Pathways

Abstract: Purpose Puerarin (PR), a Chinese medicine rich in natural components, has been reported to display anti-fibrotic, antioxidant, anti-inflammatory and immunomodulatory properties. However, the protective mechanism of PR against unilateral ureteral obstruction (UUO)-mediated renal injury is not fully clarified. Therefore, the aim of this study was to investigate the effects of PR on UUO mice and its possible mechanisms. Methods A total of 32 C57BL/6 mice were divided rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Puerarin, a natural product extracted from Radix Puerariae, has been found to have an anti-fibrotic effect in recent years, and Zhou et al found that puerarin can inhibit oxidative stress-induced tubular epithelial cell apoptosis and improve renal fibrosis by decreasing ROS production and the expression of MAPK signaling pathways in the kidneys of UUO mice [ 29 ]. Others have found that puerarin can reduce fibrosis by inhibiting the NF-κB p65/STAT3 and TGF-β/Smad signaling pathways and inhibiting the inflammation and excessive deposition of ECM in the kidney [ 30 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…Puerarin, a natural product extracted from Radix Puerariae, has been found to have an anti-fibrotic effect in recent years, and Zhou et al found that puerarin can inhibit oxidative stress-induced tubular epithelial cell apoptosis and improve renal fibrosis by decreasing ROS production and the expression of MAPK signaling pathways in the kidneys of UUO mice [ 29 ]. Others have found that puerarin can reduce fibrosis by inhibiting the NF-κB p65/STAT3 and TGF-β/Smad signaling pathways and inhibiting the inflammation and excessive deposition of ECM in the kidney [ 30 ].…”
Section: Therapeutic Effects Of Natural Products On Renal Fibrosismentioning
confidence: 99%
“…The MoA of these natural products is not corresponding to protection of skin barrier. However, several studies showed that these compounds, including puerarin, berberine, and wogonin, regulated the mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription 3 (STAT3) [70][71][72][73][74][75]. The mTOR and STAT3 signaling pathways have been known as crucial for maintaining homeostasis of skin barrier in pathophysiology of atopic dermatitis [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Renal fibrosis implies the erosion of the renal parenchyma and the accumulation of scarring, and almost all chronic and progressive kidney diseases experience this pathological pathway, which is manifested microscopically by glomerulosclerosis, tubular injury, interstitial fibrosis, and capillary rarefaction. During renal injury and chronic inflammation, increased secretion/expression of relevant enzymes and inflammatory mediators, and cytokines enable fibroblasts to differentiate towards myofibroblasts, the main responsible cells for renal fibrosis, and myofibroblast proliferation enables overexpression of α-smooth muscle actin (α-SMA), collagen (COL), fibronectin, and matrix metalloproteinases (MMP) [99][100][101][102].…”
Section: Overview Of Renal Fibrosismentioning
confidence: 99%